Medical families in the Abbasid period (132-447 A-ح 750-1055 AD) (The Bakhikhoa family as a model) - عباس رندة (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
Medical science is considered one of the sciences that the Arab Arabs mean a lot of attention as one of the main fields, in which interest emerged from behind the translation movement in particular. Where medicine witnessed a high degree of development and progress in the early Abbasid era, manifested by the scientific accomplishments of doctors, their innovative methods of diagnosing diseases and methods of treatment, the manufacture of drugs and medical compounds, and the development of a general system applied to all doctors, this is natural due to the interest of the Abbasid caliphs in science The various aspects and the translation and maintenance of the sciences of ancient civilizations, which contributed to the development of the state intellectually and culturally, and the emergence of scientific families that left their impact in stoking the spirit of thought at the time. This study aims to shed light on the scientific and cultural heritage that these families left behind regarding the cultural aspect, and the extent of their contribution in the various fields of science, especially medicine. The study covered a brief overview of medicine before the Abbasid era, then during the Abbasid era, during which the Islamic Arab State and its institutions witnessed a major development in several aspects, as well as talking about the factors affecting the development of medicine and the most important medical schools, the study also showed the most famous families that had an impact Great in enriching the cultural scene, civilizational achievements and scientific innovations in this field.